Analisis Perkembangan Tingkat Kesehatan Bpr Xyz Tahun 2014 – 2016 Dengan Menggunakan Metode Camel - Virnando Lie (Universitas Tarumanagara, 2019)
The rule of banking is very important in an economy because in its operational activities the bank has several functions, such as an intermediary functions that bridges the interests of the party who has excess fund (creditor funds) with the party in need of fund (borrower / debtor). Based on the provisions of Bank Indonesia that in order to maintain the security of cutomers, all Indonesian banking institution are obliged to report their performance to The Financial Service Authority (OJK) and always adhere to the provisions of the law prevailing in the region of Indonesia. Therefore all banking institution in Indonesia will be assessed its performance by using CAMEL Methods,with five aspects of banking assessment such as Capital, Assets, Managements, Earning and Liquidity. This assessment is quantitative descriptive research method. For the result, we used a primary data obtained through questionnaires and secondary data in the form of financial statements balance sheet and income statement of PT BPR XYZ between 2014 to 2016. According to health assessment Bank Perkreditan Rakyat (BPR), based on Decree of the Board of Directors of Bank Indonesia No.30/12/KEP/DIR/1997, The result of financial statement PT BPR XYZ of three years period (2014 – 2016) assessments and based on some benchmarks to determine the reliability of the bank after assessment of each variable, we found that the PT BPR XYZ has good banking performance (credit score more than 81 which is the minimum score of good banking performance).